Candida sp. yeast solubilizing phosphate isolated from soil in Wamena Biological Garden, Papua - ATIT KANTI (Biodiversitas Journal of Biological Diversity, 2006)
Twenty isolates of yeast were isolated from soil of Wamena Biological Garden. Out of 20 isolates tested, 3 isolates were able to increase solubility of Ca3(PO4)2), as indicated by formation of clearing zone surrounding growing colonies. Nutrient of media, which was mainly contained of glucose (20%), were metabolically converted into of either biomass or and metabolic product that may have cause a change of pH profile, and biomass during cell cultivation. Conversely, pH of media decreased during cell cultivation, and that may have cause acceleration of Ca3(PO4)2) dissolution, which have resulted in an increased of ortho-fosfat in the bulk solution during cell growth. The three isolates having ability of accelerating Ca3(PO4)2) dissolution belonging to genera of Candida. The three isolates have ability to solubilize about 5-6 mg/L-P, with phosphomonoesterase activity of about 0.10-0.65 unit. Ecological incentive of Fosfat solubilizing yeasts in soil ecosystem are enormous, among other is provision of available P for plant growth and for other soil microorganism. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: yeast, Candida, yeast solubilizing phosphate, Wamena Biological Garden.